2022
DOI: 10.1109/tvcg.2020.3021342
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Information Placement and User Representations in VR on Performance and Embodiment

Abstract: Human sensory processing is sensitive to the proximity of stimuli to the body. It is therefore plausible that these perceptual mechanisms also modulate the detectability of content in VR, depending on its location. We evaluate this in a user study and further explore the impact of the user's representation during interaction. We also analyze how embodiment and motor performance are influenced by these factors. In a dual-task paradigm, participants executed a motor task, either through virtual hands, virtual co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…The location information of small electronic devices and sensors is essential for human–computer interaction. The accurate location information of devices can give users a strong sense of experience—for example, in Virtual Reality (VR) [ 3 , 4 ] and indoor monitoring. With the development of sensing technologies, the indoor positioning tasks of electronic devices can be achieved using popular wireless infrastructures, such as commercial Wi-Fi devices, Bluetooth devices, Ultra Wide Band (UWB) devices, Radio Frequency Identification (RFID) devices, cameras, and millimeter-wave radar.…”
Section: Introductionmentioning
confidence: 99%
“…The location information of small electronic devices and sensors is essential for human–computer interaction. The accurate location information of devices can give users a strong sense of experience—for example, in Virtual Reality (VR) [ 3 , 4 ] and indoor monitoring. With the development of sensing technologies, the indoor positioning tasks of electronic devices can be achieved using popular wireless infrastructures, such as commercial Wi-Fi devices, Bluetooth devices, Ultra Wide Band (UWB) devices, Radio Frequency Identification (RFID) devices, cameras, and millimeter-wave radar.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have dealt with the relationship between bodily self-consciousness and motor performance and functioning in VR environment. A study by Seinfeld and colleagues 24 found that participants who performed the motor task through a Leap motion sensor, seeing one’s virtual hand, felt a stronger sense of body-ownership and the sense of agency and showed better task performance than those who performed the task with a keyboard and could not see one’s avatar. In relation to clinical population, Tambone and colleagues 25 demonstrated that observing the virtual body’s movements from a first-person perspective helps increase body-ownership, which subsequently promotes stroke patients' motor recovery by accessing their motor functioning.…”
Section: Introductionmentioning
confidence: 99%
“…As Kilteni et al [89] reported, this depends on various subcomponents, namely the sense of self-location (a determined volume in space where one feels to be located), the sense of agency (having the subjective experience of action, control, intention, motor selection and the conscious experience of will), and the sense of body ownership (having one's self-attribution of a body, implying that the body is the source of the experienced sensations). Other factors like the proximity of virtual objects to the body also have an effect on the sense of embodiment [188]. All these concepts (such as presence or embodiment) are intrinsic characteristics that VR can achieve, and they yield the self-consciousness feeling that makes VR so different from other media.…”
Section: Perception Of the Selfmentioning
confidence: 99%